2022
DOI: 10.1101/2022.02.25.481661
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Thermal regime during parental sexual maturation, but not during offspring rearing, modulates DNA methylation in brook charr (Salvelinus fontinalis)

Abstract: Epigenetic inheritance can result in plastic responses to changing environments being faithfully transmitted to offspring. However, it remains unclear how epigenetic mechanisms such as DNA methylation can contribute to multigenerational acclimation and adaptation to environmental stressors. Brook charr (Salvelinus fontinalis), an economically important salmonid, is highly sensitive to thermal stress, and is of conservation concern in the context of climate change. We studied the effects of temperature during p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 95 publications
0
3
0
Order By: Relevance
“…DNA methylation patterns also differ between different thermal regimes [82][83][84], and changes in global DNA methylation patterns can parallel the effects of thermal acclimation [85][86][87]. Temperature affected methylation of the myogenin promoter in Senegalese sole (Solea senegalensis), where increased DNMT3b mRNA levels at cooler temperatures were associated with increased promoter methylation, and decreased myogenin mRNA levels and muscle growth in embryos [88].…”
Section: Responses To Environmental Variation (A) 'Natural' Environme...mentioning
confidence: 99%
“…DNA methylation patterns also differ between different thermal regimes [82][83][84], and changes in global DNA methylation patterns can parallel the effects of thermal acclimation [85][86][87]. Temperature affected methylation of the myogenin promoter in Senegalese sole (Solea senegalensis), where increased DNMT3b mRNA levels at cooler temperatures were associated with increased promoter methylation, and decreased myogenin mRNA levels and muscle growth in embryos [88].…”
Section: Responses To Environmental Variation (A) 'Natural' Environme...mentioning
confidence: 99%
“…These methylation changes may have arisen due to environmental differences between benthic and limnetic habitats which could contribute to character displacement between species since the environment can have profound effects on the methylome. Previous studies have shown that methylation is affected by temperature (Ryu et al 2018;Venney et al 2022;Metzger & Schulte 2017;McCaw et al 2020;Anastasiadi et al 2017), salinity (Heckwolf et al 2020;Artemov et al 2017), rearing environment (Leitwein et al 2021;Le Luyer et al 2017;Wellband et al 2021;Gavery et al 2018), and other factors in various systems. Differences in habitat use can influence DNA methylation, as observed between capelin (Mallotus villosus) utilizing beach-and demersal-spawning life history tactics (Venney et al 2023), among sympatric Arctic charr morphs occupying different habitats and dietary niches (Matlosz et al 2022), between phenotypically divergent cichlid species (Vernaz et al 2022), and in freshwater snails (Potamopyrgus antipodarum) which exhibit differences in shell shape associated with water current speed (Thorson et al 2017).…”
Section: Epigenetic Divergence Between Whitefish Species Pairsmentioning
confidence: 99%
“…DNA methylation is the addition of a methyl group to the cytosine of CpG sites in vertebrates (a cytosine followed by a guanine in the DNA sequence), often resulting in altered transcription without a change in DNA sequence (Bird 2002). DNA methylation is sensitive to the environment and epigenetic marks are known to be affected by several factors such as temperature (Ryu et al 2020;Beemelmanns et al 2021;McCaw et al 2020;Venney et al 2022), salinity (Hu et al 2021;Artemov et al 2017;Heckwolf et al 2020), and rearing environment (Leitwein et al 2021;Le Luyer et al 2017;Wellband et al 2021;Berbel-Filho et al 2020;Venney et al 2020). DNA methylation can alter phenotype (Anastasiadi et al 2021;Vogt 2021), with evidence for phenotypically-linked epigenetic divergence associated with spawning tactics in capelin (Mallotus villosus; (Venney et al 2023) and between four sympatric Arctic charr morphs (Matlosz et al 2022).…”
Section: Introductionmentioning
confidence: 99%